Delays In the Processes of Economic Evolution - Piotr WALĄG; Kamil BOJDO (Communications of International Proceedings, 2022)
Economic evolution is recognised as a process of changes in the structures of the economy. Thus, its level is measured in time, where the delay in economic evolution processes means a slow or inhibited process of changes in the structure of economy. The problem of structural transformation processes from the point of view of determining and shaping the structure of the economy is a key area of research on the course of stages as well as the level of economic evolution. The aim of this article is to analyse the level of Poland's economic evolution as determined over time by changes in the structure of the economy. It is also hypothesized that the process of evolution of the Polish economy is significantly lagging behind the economies of highly developed countries. To achieve the objective and to verify the hypothesis, a statistical analysis of changes in the volume of employment and the structure of employment (the course and level of evolution of the Polish economy) for the developed constellation of the structure of the economy was applied. Regression analysis of estimated and calibrated models of changes in the share of manufacturing sections in total employment was also used, using the developed macroeconomic and mesoeconomic indicators (based on CSO and WTO, OECD and EUROSTAT data). The research carried out in this paper has shown the lag in the processes of economic evolution, i.e. the stage of change in the structure of the Polish economy, amounting to about 40 years to the structure of the economies of selected highly developed countries (i.e. the US, UK and DEU). Statistical research and multivariate econometric analysis made it possible to establish that such a big lag is the result of a dichotomy in the processes of the evolution of Poland's economy.
Keywords: economic evolution; structure of the economy; deindustrialization; industrialization; reindustrialization.